Kedudukan Anak Angkat Terhadap Bagian Waris Menurut Ketentuan Hukum Di Indonesia - R. Arif Muljohadi (STAI Syaichona Moh. Cholil Bangkalan, 2019)
One of the main goals of marriage is to connect offspring. But not all married couples can have children. The absence of children can be one of the triggers of disharmony in household relations. So as to maintain its integrity, husband and wife adopt children. In adoption, children will certainly have legal consequences. Moreover in Indonesian law, adoption is carried out according to Islamic law, Common law (the customary law referred to is Central Javanese Common law), and Civil law. Where the three legal systems will of course cause different legal consequences. The legal consequences are related to the position of adopted children which includes family relationships, guardianship relationships, inheritance relationships, and other relationships. Regarding inheritance relations, in Indonesia there is still pluralism including Islamic inheritance law, Customary inheritance law and inheritance law in the Civil Code. So with the variety of applicable inheritance law, also contributed to differences in the inheritance portion obtained by adopted children.